2020
DOI: 10.1016/j.apenergy.2020.114821
|View full text |Cite
|
Sign up to set email alerts
|

Design method of a compact static nonimaging concentrator for portable photovoltaics using parameterisation and numerical optimisation

Abstract: Portable solar chargers are one of the technologies that can help to achieve universal access to electricity by 2030. However, the large number of solar photovoltaic devices required and their short life-span make achieving this goal a resource and energy intensive process. To reduce the embodied energy, the embodied carbon and the human and eco-toxicity potential of portable solar chargers, solar photovoltaic concentrators can be used. This paper proposes a new nonimaging solar photovoltaic concentrator desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Figure 1 shows a cross-section of a GOCRSH concentrator. The detailed information on how to produce GOCRSH was discussed recently by Freier Raine et al [12] and will not be covered in this paper. To simplify the analysis, a specific GOCRSH concentrator design, labelled as GOCRSH_A, will be used, and its characteristics are presented in Table 1.…”
Section: Concentrator Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows a cross-section of a GOCRSH concentrator. The detailed information on how to produce GOCRSH was discussed recently by Freier Raine et al [12] and will not be covered in this paper. To simplify the analysis, a specific GOCRSH concentrator design, labelled as GOCRSH_A, will be used, and its characteristics are presented in Table 1.…”
Section: Concentrator Designmentioning
confidence: 99%
“…To simplify the analysis, a specific GOCRSH concentrator design, labelled as GOCRSH_A, will be used, and its characteristics are presented in Table 1. The Genetically Optimised Circular Rotational Square Hyperboloid (GOCRSH) concentrator was proposed by Freier Raine et al [12] for portable solar systems, and its characteristics are used in this study for the comparison between concentrated and non-concentrated solar modules. Figure 1 shows a cross-section of a GOCRSH concentrator.…”
Section: Concentrator Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The process to create a GOCRSH concentrator has been explained in detail by Freier Raine et al (2020). Specifically for the test, four type of GOCRSH concentrators were fabricated.…”
Section: Prototype Componentsmentioning
confidence: 99%
“…Based on the ray tracing analysis of the CRSH they concluded that a maximum optical concentration gain of 3.94x can be achieved. The CRSH was recently optimized using genetic algorithms, and the new design is known as genetically optimized circular rotational square hyperboloid (GOCRSH) concentrator (Freier Raine et al, 2020).…”
Section: Introductionmentioning
confidence: 99%